The role of both parents’ attachment pattern in understanding childhood obesity - Mazzeschi, Claudia; Pazzagli, Chiara; Laghezza, Loredana; Radi, Giulia; Battistini, Dalila; De Feo, Pierpaolo (Frontiers in Psychology, 2014)
Within the research area on the determinants of childhood obesity, a relatively new approach is the use of attachment theory to explore the mechanisms underlying children’s obesity risk, especially considered as emotion regulation strategies in parent-child relationship. Few are the empirical researches that have addressed this issue. The empirical investigations have used self-report measures to assess adult attachment. In attachment studies, the use of interview methods and/or performance-based instruments is advised to evaluate the entire range of possible adult attachment patterns and comprehensively explain the emotional strategies, correlates and consequences of individual differences in attachment system functioning. The aim of this study was to explore the extent to which both parents’ attachment patterns serve as self-regulative mechanisms related to childhood overweight/obesity by the Adult Attachment Projective Picture System (AAP) in a sample of 44 mothers and fathers of children referred for obesity. Insecure attachment was found as a risk factor both for mothers’ and fathers’. Also unresolved/disorganization was found to play a significant role in childhood obesity. The role of father’s attachment was explored and findings suggested considering it in etiology and treatment of childhood obesity.